Pengaruh Net Profit Margin dan Return On Equity terhadap Harga Saham dengan Earnings Per Share sebagai Variabel Moderasi - Eny Purwaningsih; Yehezkiel Setiawan Widjanarko (Research Center and Case Clearing House PPM School of Management, 2022)
LQ45 is a combined list of the most frequently traded stocks with the largest market capitalization on the Indonesia Stock Exchange. This research was performed to test the influence of Net Profit Margin and Return On Equity on Stock Price with Earnings Per Share as Moderating Variable. Data used in the research is secondary data from Indonesia Stock Exchange. The sample is 22 companies of 61 companies listed in the LQ45 index as a population. The method to test the hypothesis is multiple regression analysis using Moderated Regression Analysis (MRA). The results are that Net Profit Margin does not affect the stock price, Return On Equity does not affect the stock price, Earnings Per Share does not moderate the effect of Net Profit Margin on stock price, and Earnings Per Share moderates or strengthens the effect of Return On Equity on the stock price